2009
DOI: 10.1097/wnp.0b013e3181969017
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Onset Determination

Abstract: Digital electroencephalography has greatly expanded the opportunities for data analysis. Although commercial software packages are available they seem not to be used as widely in the preoperative work-up of epilepsy patients as might be warranted. This review will demonstrate that seizure onset can be better defined by judicious use of post hoc filter settings, expanded electrode coverage, and special electrode montages. In scalp recordings, ictal baseline shifts and infraslow activity (ISA) can be evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 36 publications
1
36
1
Order By: Relevance
“…There are increasing numbers of studies pointing to the importance of high frequency activity - HFA (Jiruska and Bragin, 2011; Jiruska et al, 2010; Jouny et al, 2007b; Rodin et al, 2009), or high frequency oscillations (HFOs) (Burns et al, 2012; Firpi et al, 2007; Jacobs et al, 2008; Jacobs et al, 2010; Jirsch et al, 2006; Nariai et al, 2011a; Ochi et al, 2007; Rampp and Stefan, 2006; Worrell et al, 2008; Worrell et al, 2004), for localizing the seizure onset zone. Recent studies have reported increased postsurgical seizure-free outcomes after resection of brain regions revealing ictal HFOs (Fujiwara et al, 2012; Jacobs et al, 2012; Jacobs et al, 2010; Modur et al, 2011; Nariai et al, 2011b; Ochi et al, 2007; Zijlmans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are increasing numbers of studies pointing to the importance of high frequency activity - HFA (Jiruska and Bragin, 2011; Jiruska et al, 2010; Jouny et al, 2007b; Rodin et al, 2009), or high frequency oscillations (HFOs) (Burns et al, 2012; Firpi et al, 2007; Jacobs et al, 2008; Jacobs et al, 2010; Jirsch et al, 2006; Nariai et al, 2011a; Ochi et al, 2007; Rampp and Stefan, 2006; Worrell et al, 2008; Worrell et al, 2004), for localizing the seizure onset zone. Recent studies have reported increased postsurgical seizure-free outcomes after resection of brain regions revealing ictal HFOs (Fujiwara et al, 2012; Jacobs et al, 2012; Jacobs et al, 2010; Modur et al, 2011; Nariai et al, 2011b; Ochi et al, 2007; Zijlmans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The role of high frequency activity - HFA (Jiruska and Bragin, 2011; Jiruska et al, 2010; Jouny et al, 2007b; Rodin et al, 2009) or high frequency oscillations - HFOs (Worrell et al, 2008; Worrell et al, 2004) in epilepsy has been extensively investigated recently, and has been reported to be temporally and spatially correlated to the seizure onset zone. During ictal recordings, HFOs were recently observed mostly in the region of seizure onset, and less frequently in areas of secondary spread (Jirsch et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[46] In cats with penicillin-induced seizure foci, similar DC shifts were noted to be characterized by a horizontal dipole, having maximum amplitude at the focus with the field extending to about 10 mm. [47] In the early studies, DC shifts were not seen on conventional EEG recordings obtained from the AC amplifiers, possibly because of the short time constant of 0.3 s (~0.53 Hz low frequency filter) used during that time,[1] giving rise to the notion that dedicated DC amplifiers were needed to record such activity. However, Ikeda et al .…”
Section: Ibss and Isamentioning
confidence: 99%
“…[1] This mainly stems from technological advances that have allowed us to record, store and analyze large amounts of human EEG data with relative ease using sophisticated hardware and commercially available software packages. The progress in data acquisition and analysis has occurred in conjunction with several groundbreaking studies demonstrating the clinical utility of EEG activity >70 Hz, termed high frequency oscillations (HFOs).…”
Section: Introductionmentioning
confidence: 99%
“…Some assess the performance based on a heuristically derived static data division to training and testing datasets (Mitra et al, 2009; Navakatikyan et al, 2006; Aarabi et al, 2007), others perform statistical tests by dividing the data repeatedly to training and testing (Temko et al, 2011; Greene et al, 2008), while others do not have separate testing data at all and report results over the data on which the algorithm was developed (Deburchgraeve et al, 2008). Last but not least, not all studies (Mitra et al, 2009) clearly report the complete etiology and gestational age (GA) of the babies used in the dataset and do not include seizure etiology e.g. hypoxic ischemic encephalopathy or whether the dataset consists of full-term or pre-term babies – this complicates the selection of the best existing algorithm for a designated group of patients in NICU.…”
Section: Introductionmentioning
confidence: 99%